2014
DOI: 10.1016/j.fcr.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in the uptake, partitioning and remobilisation of nitrogen during grain-filling in wheat

Abstract: HighlightsTwenty elite varieties of wheat grown at 2 N-rates in a field experiment at Rothamsted, UK.To quantify genetic variation in uptake, partitioning and remobilisation of N during grain-filling.Significant genetic variation in yield and %N, and in N-uptake, organ N-contents and N remobilised from straw to grain.N remobilised from vegetative organs with high levels of efficiency (80–85%).No strong correlations between N-related plant parameters (e.g. stem-N) and crop performance at a given N-rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 21 publications
7
81
0
11
Order By: Relevance
“…It was observed a direct effect (DE) with sign and magnitude similar to the correlation coefficient (r) of the NRE over the NUE under low (DE = 0.94, r = 0.617) and high (DE = 0.65, r = 0.721) N supply, corroborating the studies of Barraclough et al (2014), Guo et al (2014) and Le Gouis et al (2000). Although NUtE has been associated with the NUE (r = 0.487 and r = 0.516), this was mainly due to indirect effects (IE) of NRE (IE = 0.587) under low N supply.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It was observed a direct effect (DE) with sign and magnitude similar to the correlation coefficient (r) of the NRE over the NUE under low (DE = 0.94, r = 0.617) and high (DE = 0.65, r = 0.721) N supply, corroborating the studies of Barraclough et al (2014), Guo et al (2014) and Le Gouis et al (2000). Although NUtE has been associated with the NUE (r = 0.487 and r = 0.516), this was mainly due to indirect effects (IE) of NRE (IE = 0.587) under low N supply.…”
Section: Resultssupporting
confidence: 86%
“…The highest protein concentrations in the grain are related to the higher remobilization of post-anthesis N (Barraclough et al 2014;Bogard et al 2010). According to Kichey et al (2007), much of the N found in grains comes from the remobilization of N stored in the shoots and roots of the plant before anthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar protein content in triticale varieties has been previously reported: Tohver et al (2005) reported 9.7-14.5 g·100 g -1 depending on genotype grown in Northern conditions, Rakha et al (2011) observed 11.7-15.7 g·100 g -1 depending on cultivar and growing site; and Fraú et al (2016) reported 11.8-15.2% depending on cultivar (Fraú et al, 2016). The observed inverse relationship between grain yield and protein content in our study was previously reported by several researchers (Martre et al, 2003;Barraclough et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Gaju et al (2011) also reported genetic variability in NUE under low N application rate due largely to differences in NUtE rather than NUpE. Studies indicate that the development and use of wheat cultivars with higher NUE can contribute to a reducing the amount of nitrogen to be applied without decreasing grain yield (Barraclough et al, 2014;Gaju et al, 2014). Therefore, understanding the physiological basis of variations among wheat cultivars in NUtE may offer avenues to increase NUE for enhancing whaet yield in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%